2001
DOI: 10.1518/001872001775870403
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Decision Making and Action Selection under Time Pressure and Uncertainty: The Case of In-Flight Icing

Abstract: Operators in high-risk domains such as aviation often need to make decisions under time pressure and uncertainty. One way to support them in this task is through the introduction of decision support systems (DSSs). The present study examined the effectiveness of two different DSS implementations: status and command displays. Twenty-seven pilots (9 pilots each in a baseline, status, and command group) flew 20 simulated approaches involving icing encounters. Accuracy of the decision aid (a smart icing system), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 19 publications
6
114
0
1
Order By: Relevance
“…While instructional displays have demonstrated some utility in a number of work-related application areas (e.g., Sarter and Schroeder, 2001), evidence on the benefits of support aids providing qualitative feedback is generally rather more equivocal than for the benefits of predictive aids. Experts systems provide a good example of the genre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While instructional displays have demonstrated some utility in a number of work-related application areas (e.g., Sarter and Schroeder, 2001), evidence on the benefits of support aids providing qualitative feedback is generally rather more equivocal than for the benefits of predictive aids. Experts systems provide a good example of the genre.…”
Section: Discussionmentioning
confidence: 99%
“…These are similar to command displays in that both give explicit instructions of how to proceed. Research has indicated a number of circumstances under which command displays have provided benefits, such as high time pressure in a decision-making situation (Sarter and Schroeder, 2001). In the context of the CHS operation, there were indications that some users did not have adequate strategies available to manage the system more energyefficiently although they were aware of their undue energy consumption (Sauer et al, 2007).…”
Section: Instructional Displaysmentioning
confidence: 99%
“…This resistance recalls the disinclination noted in our field to the use of decision support systems such as executive information systems (Elam and Leidner 1995;Hung 2003). Unless perfect reliability of the decision aid can be assumed, there is evidence that simple status displays may actually be preferable to instructional displays (Sarter and Schroeder 2001), which can give misleading advice.…”
Section: Display Design and User Supportmentioning
confidence: 99%
“…Time pressure, defined here as the frequency with which the decision maker is faced with new information to be processed within a certain time period, has been shown to reduce the quality of decision-making (Payne et al, 1993) in studies spanning a variety of contexts (e.g., Aminilari and Pakath, 2005;Kocher and Sutter, 2006;Lin and Su, 1998;Sarter and Schroeder, 2001;Thomas and Wickens, 2006). Prior research suggests that decision makers under increased time pressure gather less information and process it faster, causing some individuals to use simplifying heuristics to reduce effort, potentially lowering decision accuracy (e.g., Lin and Su, 1998;Payne et al, 1988;Payne et al, 1996;Tversky, 1972).…”
Section: Time Pressurementioning
confidence: 99%